2006
DOI: 10.1177/070674370605100304
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and its Prevention among Older Adults

Abstract: A dults aged 65 years or over have high rates of suicide worldwide (1). Approximately 1.3 die by suicide in Canada every day (2). Older adults have long had high suicide rates (3-7); however, programmatic study of geriatric suicide is relatively recent. The prevalence of late-life suicides may increase as the baby boom cohort reaches retirement age (8), given this population's high suicide rates (9,10) and because they are moving into a phase of life in which rates are high. However, baby boomers' strength in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 128 publications
0
41
0
4
Order By: Relevance
“…We have theorized that protective factors may not simply reflect an absence of suicide risk, but rather may enhance psychological well-being and confer psychological resiliency to mental disorders and risk for suicide [4]. Research is needed assessing whether perceived connectedness to friends, peers, or other supports protects against suicide ideation, and whether participation in social activities, seniors centers, and/or religious activities increases community connectedness and helps protect against death by suicide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have theorized that protective factors may not simply reflect an absence of suicide risk, but rather may enhance psychological well-being and confer psychological resiliency to mental disorders and risk for suicide [4]. Research is needed assessing whether perceived connectedness to friends, peers, or other supports protects against suicide ideation, and whether participation in social activities, seniors centers, and/or religious activities increases community connectedness and helps protect against death by suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on suicide among middle-aged and older adults has focused on risk factors rather than on factors that protect against death by suicide [4], necessitating research on psychosocial variables that might reduce the likelihood of contemplating suicide when experiencing adversity. Elevated suicide risk is associated with previous self-injury, presence of suicide ideation, mood disorders and other forms of psychopathology, physical illness and functional impairment, personality characteristics such as rigidity and tendency toward emotional instability, and psychosocial problems, stressors, and difficulty adjusting to life transitions [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Theory and research suggest that attention to suicide risk factors may be insufficient to identify and intervene effectively with at-risk individuals. Following the call for a complementary focus on resiliency [20], we demonstrated that older adults expressing greater perceived meaning in life (MIL) and life satisfaction reported significantly less suicide ideation [21]. The positive effect of MIL was most robust at higher levels of depressive symptom severity [22].…”
mentioning
confidence: 99%